G is for genes : the impact of genetics on education and achievement - Asbury, Kathryn; Plomin, Robert, 1948- (Chichester, West Sussex : Wiley Blackwell, 2014)
"G is for Genes shows how a dialogue between geneticists and educationalists can have beneficial results for the education of all children--and can also benefit schools, teachers, and society at large.-Draws on behavioral genetic research from around the world, including the UK-based Twins' Early Development Study (TEDS), one of the largest twin studies in the world -Offers a unique viewpoint by bringing together genetics and education, disciplines with a historically difficult relationship -Shows that genetic influence is not the same as genetic determinism and that the environment matters at least as much as genes -Designed to spark a public debate about what naturally-occurring individual differences mean for education and equality"--
Part one. In theory -- part two. In practice.
Edition statement from running title area.
Includes bibliographical references and index.
Online resource; title from PDF title page (Wiley, viewed November 12, 2013).
Keywords: Learning ability -- Genetic aspects; Academic achievement; Behavior genetics; PSYCHOLOGY -- Education & Training; EDUCATION -- Essays; EDUCATION -- Organizations & Institutions; EDUCATION -- Reference; Academic achievement; Behavior genetics; Learning ability -- Genetic aspects; Electronic books; Electronic books